2012
DOI: 10.1292/jvms.11-0549
|View full text |Cite
|
Sign up to set email alerts
|

Three Minimally Invasive Methods of Measuring of Portal Vein Pressure in Healthy Dogs

Abstract: ABSTRACT. We compared wedged hepatic venous pressure (WHVP), splenic pulp pressure (SPP) and trans-splenic portal vein pressure (TSPVP) in healthy dogs. We found that portal blood pressure could be measured in dogs using any of these techniques. The WHVP, SPP and TSPVP were 7.8 ± 1.0, 6.2 ± 0.8 and 6.8 ± 1.2 mmHg, respectively. Measuring SPP using ultrasound is most simple and minimally invasive, and it might be useful for evaluating portal hypertension in dogs with liver diseases. KEY WORDS: canine, catheteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Gross visualization identified APSCs around the left kidney in 5 of 17 dogs. The SPP was measured in 7 of 17 dogs and found to be in the range of 5–13 (median, 7) mmHg; 2 of 7 dogs with formation of APSCs had SPP of 8 and 13 mmHg, which is considered high in comparison with previously reported mean SPP of 6.2 ± 0.8 mmHg in healthy dogs . There were no instances of positive bacterial growth in the 7 of 17 dogs in which liver tissue samples were obtained.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Gross visualization identified APSCs around the left kidney in 5 of 17 dogs. The SPP was measured in 7 of 17 dogs and found to be in the range of 5–13 (median, 7) mmHg; 2 of 7 dogs with formation of APSCs had SPP of 8 and 13 mmHg, which is considered high in comparison with previously reported mean SPP of 6.2 ± 0.8 mmHg in healthy dogs . There were no instances of positive bacterial growth in the 7 of 17 dogs in which liver tissue samples were obtained.…”
Section: Resultsmentioning
confidence: 54%
“…The SPP was measured in 7 of 17 dogs and found to be in the range of 5-13 (median, 7) mmHg; 2 of 7 dogs with formation of APSCs had SPP of 8 and 13 mmHg, which is considered high in comparison with previously reported mean SPP of 6.2 AE 0.8 mmHg in healthy dogs. 25 There were no instances of positive bacterial growth in the 7 of 17 dogs in which liver tissue samples were obtained. Ovariohysterectomy was performed concurrently in 8 of 17 dogs and an ameroid constrictor was placed in 1 of 17 dogs with CPSS.…”
Section: Resultsmentioning
confidence: 89%
“…The most common complication of cirrhosis is ascites, which may result either from severe portal hypertension or combination of moderately increased portal blood pressure and hypoalbuminemia (Arroyo and Colmenero, 2003;Sakamoto et al, 2012;Zhai et al, 2015). It is also reported that resistances to hepatic and renal arterial blood flows increases in cirrhotic patients (Rivolta et al 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with dilutional hyponatremia, refractory ascites and hepatorenal syndrome is extremely poor. Therefore, several studies have been carried out to determine both systemic hemodynamics and renal function for predicting the survival in humans (Arroyo and Colmenero, 2003;Sakamoto et al, 2012;Zhai et al, 2015). The occurrence of these diseases in dogs are unknown due to the absence of adequate studies in veterinary field (Lamb et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Atypical hepatectomies, especially partial or complete lobar resections, require an accurate knowledge of the internal liver structures (Bismuth, ; Niza et al., ). Liver haemodynamics in the dog, especially regulation of the portal venous blood flow and pressure both to the liver and within the liver, have been investigated in many studies (Colle et al., ; Sartor et al., ; Dave et al., ; Sakamoto et al., ). This knowledge is of paramount importance when the blood supply within the liver is modified, for example by portosystemic shunts or liver surgery (Lee et al., ; Furneaux, ).…”
Section: Introductionmentioning
confidence: 99%